SIMBOL WAKTU DALAM KUMPULAN PUISI ASMARADANA KARYA GOENAWAN MOHAMAD - Efendi, Anwar (Diksi, 2005)
Goenawan Mohamad's poems have interestingcharacteristics especially in the use of idiomatic and symbolicexpressions related to the dimension of time. In addition, his specialthematic choices involving human beings within the frame of thetime flow enable his poetry to say many things.It is the nature of human beings to be between a beginningand end points in time, the former signifying a process from beingnonexistent to being existent at birth and the latter from beingexistent back to being nonexistent at death. A description of time aspart of human beings' journey of life is what is often presented inGoenawan Mohamad's poems.Keywords: time, monochronic, polychronic